Effective communication for relational coordination in remote work: How job characteristics andHRpractices shape user–technology interactions - Fuchs, Christina; Reichel, Astrid (Human Resource Management, 2023)
AbstractThe theory of relational coordination holds that frequent, timely, accurate, and problem‐solving communication positively interacts with relationships of mutual respect, shared goals, and shared knowledge to support effective work coordination. With increasing numbers of employees working remotely, Advanced Communication Technologies (ACTs) are crucial for enabling the communication necessary for relational coordination. To investigate how organizations can maintain effective communication between employees in remote work settings, we conducted 47 interviews across multiple organizations. We find that users enact different affordances, that is, action possibilities, of the same material features of an ACT. Enacting these affordances supports frequent, timely, accurate, and problem‐solving communication when working remotely. Which affordances users enact varies systematically with job characteristics. Specifically, users whose jobs have high levels of task variety, autonomy, creative problem solving, and interdependence across teams enact more of the affordances that enable effective communication. Comprehensive ACTs that integrate all communication features into one technology and rules requesting the company‐wide exclusive interaction with this ACT strengthen the relationship between users' job characteristics and affordance enactment. Our findings show that it is important to involve HRM from the outset so that, in close cooperation with IT, a system can be found that—supported by suitable sets of rules—enables effective communication.